Balanced Electrolyte Solutions Versus 0.9% Saline for Kidney Transplantation: An Updated Systematic Review and Meta-analysis - Susan S. Wan, MBBS, MMed (Clin Epi), FRACP, PhD; Kate Wyburn, MBBS, FRACP, PhD; Steven J. Chadban, PhD, FRACP, FAHMS; Michael G. Collins, MBChB, FRACP, PhD (Transplantation Direct)
Background. Perioperative intravenous fluids are administered to kidney transplant recipients to maintain hemodynamic stability and graft perfusion; however, the ideal fluid remains uncertain. Although 0.9% saline (saline) is commonly used, its high chloride content causes hyperchloremic metabolic acidosis and may increase the risks of delayed graft function (DGF) and hyperkalemia. Balanced electrolyte solutions (BES) have a more physiological chloride concentration and may reduce these risks. Previous meta-analyses found insufficient evidence to compare BES with saline for these outcomes; however, new studies have recently been published. In this updated review, we compared the effects of BES with saline on the risk of DGF and hyperkalemia in kidney transplantation. Methods. MEDLINE, Embase, and CENTRAL were searched for randomized controlled trials comparing BES with saline in kidney transplantation. The primary outcomes were DGF and hyperkalemia. Eligible studies were assessed for risk of bias and data were pooled for analysis. The Grading of Recommendations Assessment, Development, and Evaluation framework was used to assess the quality of evidence. Results. Ten studies involving 1532 participants were included. The quality of evidence was high for deceased donor transplantation and very low for living donor transplantation. The relative risk (RR) of DGF associated with BES compared with saline was 0.83 (95% confidence interval [CI], 0.71-0.96; P = 0.01) in deceased donor transplantation. There was no difference in DGF in living donor transplantation (RR 0.79; 95% CI, 0.26-2.41; P = 0.68). There was no difference in hyperkalemia between groups (RR 0.87; 95% CI, 0.59-1.27; P = 0.46). Conclusions. Compared with saline, BES reduces the risk of DGF in deceased donor kidney transplantation without increasing hyperkalemia.